2021
DOI: 10.1002/acm2.13447
|View full text |Cite
|
Sign up to set email alerts
|

Corrections of photon beam profiles of small fields measured with ionization chambers using a three‐layer neural network

Abstract: The purpose of this work is to study the feasibility of photon beam profile deconvolution using a feedforward neural network (NN) in very small fields (down to 0.56 × 0.56 cm 2 ). The method's independence of the delivery and scanning system is also investigated. Lateral beam profiles of photon fields between 0.56 × 0.56 cm 2 and 4.03 × 4.03 cm 2 were collected on a Siemens Artiste linear accelerator. Three scanning ionization chambers (SNC 125c, PTW 31021, and PTW 31022) of sensitive volumes ranging from 0.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…However, the neural network was trained exactly on the accelerator and the training data was a subset of the data used for validation. The same applies to the publications by Mund et al (2020Mund et al ( , 2021, Schönfeld et al (2021). Also in these studies, direct measurement data were used for training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the neural network was trained exactly on the accelerator and the training data was a subset of the data used for validation. The same applies to the publications by Mund et al (2020Mund et al ( , 2021, Schönfeld et al (2021). Also in these studies, direct measurement data were used for training.…”
Section: Discussionmentioning
confidence: 99%
“…The other approach to solve the penumbra problem is an AI-based solution. Several studies (Liu et al 2018, Mund et al 2020, Schönfeld et al 2021 have demonstrated an AI-based approach where an AI was trained with a training dataset of profile data measured with an ionization chamber as well as undisturbed profile measurements measured with a silicon detector. However, this approach requires a huge amount of training data, which has to cover many different conditions, such as energy, depth, accelerator type to avoid overfitting.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several researchers have modelled various linac machines using MC simulation. For these simulations, general purpose MC software like EGSnrc [33][34][35], GEANT4 [36][37][38][39], PENELOPE [40][41][42], MCNP [43][44][45][46], … have been widely used [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Artiste linac offers a comprehensive collection of advanced capabilities including image-guided protocols and treatment delivery modalities. Although Siemens left the radiotherapy market, this machine is still used in many radiotherapy departments [49][50][51] especially in the west Asia and other developing countries. Many radiotherapy and oncology centers in our region are currently using this model of linear accelerator to perform their clinically routine treatments [52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the recovery of the dose profile from measured signal profile using a feed-forward artificial neural network (NN) has been demonstrated (Liu et al 2018). The application of NN has been generalized to other beam qualities (Mund et al 2020) and smaller field sizes (Schönfeld et al 2021) showing promising results. Nevertheless, large dataset is usually necessary to feed the training process of these NN.…”
Section: Introductionmentioning
confidence: 99%